Toward more realistic viscosity measurements of tyre rubber–bitumen blends - Lo Presti, Davide; Fecarotti, Claudia; Clare, Adam T.; Airey, Gordon (Elsevier, 2014)
The measurement of rheological properties of the tyre rubber bitumen blends is often challenging due to presence of suspended tyre rubber’s crumbs. Furthermore, the phase separation during the course of measurements makes the viscosity of these non-homogeneous blends difficult to ascertain. In this study, a new dual helical impeller was designed and manufactured to be used with a rotational viscometer in order to have a real-time control of the viscosity while performing a laboratory mixing of the blends. Layer based manufacturing techniques showed to be a convenient method to produce complex shaped impeller prototypes before manufacturing the more expensive stainless steel assembly. Impeller geometry was optimised to create a convective like flow within the sample and so minimise phase separation. Shear rate constant is geometry dependent and a calibration exercise was carried out to ascertain this. Results of both calibration and validation phases showed that the new impeller provides reliable viscosity measurements of homogenous fluids such as neat bitumen. With regards to complex fluids the new impeller showed a more stable and realistic trend than that obtained by using a standard spindle. In fact, it was demonstrated that the new impeller significantly decreases phase separation within the blend and in turns provides a more realistic measurement of the viscosity. This system represents a feasible and improved solution for optimising the laboratory modification process of tyre rubber bitumen blends by adapting the rotational viscometer as a low-shear mixer.